Assessment of Knowledge Regarding Oral Hygiene among Parents of Pre-School Children Attending Pediatric Out Patient Department in Dhulikhel Hospital - Khanal, K; Shrestha, D; Ghimire, N; Younjan, R; Sanjel, S (Kathmandu University Medical Journal, 2015)
Background Level of knowledge regarding oral hygiene among the parents of pre-school children plays an important role on maintaining the good oral hygiene of their children. In Nepal, sufficient research has not been carried out on this area. Objective Objective of this study is to assess the level of knowledge on oral hygiene of pre-school children’s parents attending pediatric outpatient department in Dhulikhel Hospital. Method A descriptive study was conducted from November 2012 to January 2013 among one hundred parents of preschool children visiting pediatrics outpatient department of Dhulikhel Hospital. Paper and pencil based semi structured questionnaire was used for collecting data. Questions related to demographic information and knowledge were asked. Thirty questions were used for assessing knowledge level. Knowledge score was calculated by allocating one point for each correct answer and zero point for each wrong answer. Analyzed data were presented in terms of numbers and percentages. Total knowledge scores were categorized based on percentage. Knowledge score was categorized on four group - exclusive intervals - namely-poor (0-40%), moderate (40-60%), good (60-80%) and excellent (80-100%). Mann-Whitney U test and Kruskal-Wallis test were applied to check significance difference and chi-square test was used to check association among different background characteristic. Result It was found that 81% had moderate knowledge, 15% had poor knowledge and 4% had good knowledge about oral hygiene. Median knowledge score was found to be 15 with range 10 to 21. Following variables were found to be significant difference on knowledge category: Education status (p<0.001), education level (p= 0.041), past experience about oral health problem (p = 0.008), Further significant association was found between knowledge category and educational status (p < 0.001) and between knowledge category and past experience (p < 0.001). Conclusion Knowledge regarding oral hygiene was found satisfactory among the parents of preschool children visiting pediatric OPD of Dhulikhel Hospital. Kathmandu University Medical Journal Vol.13(1) 2015; 38-43